Psychological testing in schools an assessment - Lazo, Lucita S. ([Metro Manila] Psychological Association of the Philippines, 1977)
Assessed the status of psychological testing in Philippine government, private, and special educational institutions in terms of tests administered, purpose of test administration, training received by administrator, and ratings on test usefulness. It is observed that with respect to (a) percentage of institutions engaged in testing and (b) the development of scientific literature, the educational sector is ahead of the clinical and industrial sectors.
Includes bibliographical references(page 26-27)
Keywords: Psychology Philippines -- Periodicals